Dampak Media Audio Visual terhadap Pengetahuan Ibu Mengenai Stunting pada Balita di Dusun Waiselang Tahun 2024 - Ety Dusra (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Stunting remains a serious public health issue in Indonesia. It not only affects the physical condition of children but also impairs cognitive development and long-term performance due to suboptimal brain development. Nationally, the prevalence of stunting is still high. According to the 2023 Indonesian Health Survey (SKI), the national stunting rate is 21.5%. This study aims to determine the effect of audiovisual media on improving mothers' knowledge about stunting in Waiselang Hamlet. The research uses a quantitative approach with a pre-experimental design, specifically a one-group pre-test and post-test design. The study population consists of 45 mothers with toddlers, all of whom were included as samples using total sampling technique. The instrument used was a questionnaire consisting of a series of statements. Data analysis was carried out using the Wilcoxon test. Based on the Wilcoxon test results, there was an increase in respondents’ knowledge after being given education using audiovisual media. The influence of audiovisual education, according to the Wilcoxon test, resulted in a p-value of 0.000, indicating a significant effect of audiovisual media-based education on increasing mothers' knowledge about stunting in toddlers.